1998
DOI: 10.1016/s0375-9474(97)00637-4
|View full text |Cite
|
Sign up to set email alerts
|

Screening effects on the elastic nucleon-nucleon cross section in relativistic nuclear matter

Abstract: We investigate the screening effects on the nucleon-nucleon elastic cross section inside nuclear matter at zero and finite temperature. The N-N interaction is described phenomenologically via meson exchanges (σ, π and ω) in the framework of a relativistic lagrangian model. The expressions for the in-medium meson propagators, which take into account the effects of matter polarization and renormalized vacuum polarization, are used in the calculation of the various meson contributions to the total cross section i… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

1998
1998
2016
2016

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 70 publications
1
9
0
Order By: Relevance
“…1 Our claim is that RPA may give important effects, both quantitative and qualitative, and has to be considered in many-body calculations of nuclear matter. As a matter of fact, it was shown [13] that RPA corrections give rise to a modification of the in-medium cross section of the same order of magnitude as Brueckner ones, and compatible with experimental data available so far. Other examples are the reduction of neutrino opacities in neutron star matter from RPA corrections of the NN interaction [14,15] and the measurement of the electromagnetic response function in quasielastic electron scattering experiments [16].…”
Section: Introductionsupporting
confidence: 84%
“…1 Our claim is that RPA may give important effects, both quantitative and qualitative, and has to be considered in many-body calculations of nuclear matter. As a matter of fact, it was shown [13] that RPA corrections give rise to a modification of the in-medium cross section of the same order of magnitude as Brueckner ones, and compatible with experimental data available so far. Other examples are the reduction of neutrino opacities in neutron star matter from RPA corrections of the NN interaction [14,15] and the measurement of the electromagnetic response function in quasielastic electron scattering experiments [16].…”
Section: Introductionsupporting
confidence: 84%
“…Indeed, the angular dependence of the cross section can be modified by the in-medium effects, and this modification is model dependent (e.g. Refs [40,41,51]). …”
Section: ρN−ρp ρN+ρpmentioning
confidence: 99%
“…Refs [51]). To consider the uncertainty of the in-medium differential cross section, three commonly used differential NN cross sections in transport models are adopted and given as follows:…”
Section: Model Descriptions and Observablesmentioning
confidence: 99%
“…for the mixing, longitudinal and transverse parts. The explicit expression for the polarizations and a study of the dispersion relations can found in [11,13]. Besides the σ and longitudinal and transverse ω branches, there is a zero sound branch in the mixed σ-ω mode.…”
Section: The Modelmentioning
confidence: 99%
“…The concern of our present work is to release this assumption. We refer the reader to [11] for details on the formalism and only recall here the main formulaes.…”
Section: Introductionmentioning
confidence: 99%